The Performance Of Enterpreneurships Skills Among Belawai Women In Sarawak, Malaysia Through Collective Actions. - Selamat, N.H.; Abd. Gapor, S. (2006)
This paper reveals the womens' socio-economic activities in the Belawai fishing village, located at the coastal areas of Sarawak, Malaysia.